Relationship between telomerase activity and parameters of carbohydrate metabolism and vascular wall - N. V. Brailova; E. N. Dudinskaya; O. N. Tkacheva; N. V. Sharashkina; I. D. Strazhesco; D. U. Akasheva; M. V. Shestakova (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the relationship between telomerase activity and parameters of carbohydrate metabolism and vascular wall depending on the type 2 diabetes (T2D).Material and methods. The study included 50 patients with T2D and 139 healthy volunteers. All subjects were assessed for carbohydrate metabolism, chronic inflammation (C-reactive protein (CRP), fibrinogen), endothelial dysfunction, carotid intima-media thickness and number of atherosclerotic plaques by duplex scanning, carotid-femoral pulse wave velocity, lymphocyte telomere length and telomerase activity.Results. In T2D patients, telomerase activity was lower (p=0,039), telomeres were shorter (p=0,031) and CRP level was higher (p=0,031) than in patients without T2D. All patients were divided by telomerase activity. T2D patients with low telomerase activity had higher values of CRP (р=0,016), pulse wave velocity (р=0,010), carotid intima-media thickness (р<0,001) and number of atherosclerotic plaques (р=0,014) than in patients without T2D. There were no significant differences in high telomerase activity group. In the group of patients with/without T2D, there were independent negative relationship between telomerase activity and glycated hemoglobin (p=0,035), fasting plasma glucose (p=0,003), arterial stiffness (p=0,044) and independent positive relationship between telomerase activity and fibrinogen (p=0,027), CRP (p=0,042).Conclusion. Vascular changes, chronic inflammation and cell aging were weightier in patients with T2D. The established relationship between telomerase activity and parameters of carbohydrate metabolism, chronic inflammation and vascular stiffness may indicate the important role of telomerase activity in the development of cardiovascular diseases in T2D patients.